Lipoprotein (a) and other Lipid Profile in Patients with Thrombotic Stroke: Is it a Reliable Marker? - Nagaraj, Shashidhar K; Pai, Pareenta; Bhat, Gopalakrishna; A., Hemalatha (Journal of Laboratory Physicians, 2011)
Background: Cerebrovascular disease (CVD) and coronary heart disease (CHD) cause 40%-50% of deaths in developed countries with CVD causing 10%-12% of deaths. Though increased Lipoprotein (a) is a risk factor in developing CHD, its role is poorly defined in etiopathogenesis of CVD.Aims: To find the association of lipoprotein (a) and lipid profile in thrombotic stroke patients after acute phase.Settings and Design: The study was conducted at Kasturba Medical College, Manipal. Twenty one cases of thrombotic stroke and 18 cases of age and sex matched controls were taken for the study. Informed consent was taken from both case and control.Materials and Methods: Overnight fasting sample was collected from both case and control. Serum was separated and parameters such as total cholesterol, triglycerides, high density lipoproteins-C, low density lipoprotein-C, lipoprotein (a), fasting blood sugars were estimated. Statistical analysis: Data were analyzed by SPSS software, Student′s t-test, standard deviation (SD), and standard error of mean (SEM), P-value <0.05 is considered to be significant.Results: In this study, we found no statistical significant differences in serum lipid and lipoprotein (a) profile between controls and thrombotic stroke patients.Conclusions: Highest frequency (38%) of stroke was found in the age group of 7080 years. There were other associated risk factors such as diabetes in five cases (24%), hypertension in nine cases (43%), and family history of stroke in four cases. However, further studies are required to evaluate the importance of serum Lp(a) estimation in the assessment as a risk factor for thrombotic stroke.
Keywords: Lp(a); lipid profile; thrombotic stroke